Binding and Action of Triphenylphosphonium Analog of Chloramphenicol upon the Bacterial Ribosome - Chih-Wei Chen; Julia A. Pavlova; Dmitrii A. Lukianov; Andrey G. Tereshchenkov; Gennady I. Makarov; Zimfira Z. Khairullina; Vadim N. Tashlitsky; Alena Paleskava; Andrey L. Konevega; Alexey A. Bogdanov; Ilya A. Osterman; Natalia V. Sumbatyan; et al. (MDPI AG, 2021)
Chloramphenicol (CHL) is a ribosome-targeting antibiotic that binds to the peptidyl transferase center (PTC) of the bacterial ribosome and inhibits peptide bond formation. As an approach for modifying and potentially improving the properties of this inhibitor, we explored ribosome binding and inhibitory properties of a semi-synthetic triphenylphosphonium analog of CHL-CAM-C4-TPP. Our data demonstrate that this compound exhibits a ~5-fold stronger affinity for the bacterial ribosome and higher potency as an in vitro protein synthesis inhibitor compared to CHL. The X-ray crystal structure of the Thermus thermophilus 70S ribosome in complex with CAM-C4-TPP reveals that, while its amphenicol moiety binds at the PTC in a fashion identical to CHL, the C4-TPP tail adopts an extended propeller-like conformation within the ribosome exit tunnel where it establishes multiple hydrophobic Van der Waals interactions with the rRNA. The synthesized compound represents a promising chemical scaffold for further development by medicinal chemists because it simultaneously targets the two key functional centers of the bacterial ribosome-PTC and peptide exit tunnel.